MQA's D-SETARA - Rates the disciplines offered by higher education institutions - New Sabah Times English, (KK) (New Sabah Times English (KK), 2013)
Malaysian Qualifications Agency (MQA) has developed and implemented a new rating system known as The Discipline-Based Rating System (DSETARA)to assess (by areas of discipline) the quality of teaching and learning in Higher Education Institutions (HEIs) in Malaysia. It aims to ensufe continuous improvement to the quality and competitiveness of higher learning institutions. This rating covers four disciplines: Engineering; Tourism and Hospitality; Medical, Dental and Pharmacy and Health Sciences. MQA is working on other disciplines.